Rohingyas in Bangladesh and Myanmar : quest for a sustainable solution - Iftekharul Bashar (2012)
Bangladesh, under international pressure to receive Rohingya refugees from Myanmar, has its own domestic concerns of demographic pressure, resource scarcity, and internal security. For a sustainable solution, the international community needs to assist Myanmar in human development and community engagement for building durable peace in its troubled Rakhine state.